2014
DOI: 10.1007/s11060-014-1525-z
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care in adult medulloblastoma: results of an international online survey

Abstract: The literature on medulloblastoma in adults is generally limited to case reports and retrospective series, and there is no accepted standard of care. The Cooperative Trials Group for Neuro-Oncology (COGNO) sought to determine the range and consistency of clinicians' approaches to management as a basis for future trials. We aimed to identify current treatment strategies for adult medulloblastoma through an online survey launched at the 2012 Society of Neuro-Oncology meeting and by email invitation. Clinicians w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Due to their rarity, prospective trials on adult medulloblastomas are limited [40]. The management of adult medulloblastomas is adapted from paediatric protocols, often resulting in dose-limiting toxicities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their rarity, prospective trials on adult medulloblastomas are limited [40]. The management of adult medulloblastomas is adapted from paediatric protocols, often resulting in dose-limiting toxicities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Practice variation across adult and pediatric providers has been reported in other soft tissue cancers as well. For example, a survey of adult and pediatric oncologists on the treatment of adult medulloblastoma patients similarly demonstrated substantial variation in practice, particularly with the choice of chemotherapeutic agents, likely reflecting the limited data available relevant to older adult population [ 22 ]. Likewise, population studies have demonstrated less aggressive protocols for diagnosis, staging, and treatment for adults with Wilms' Tumor relative to their pediatric counterparts and cited this less aggressive approach as an explanation for inferior survival outcomes among adults [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the relatively low incidence of adult MBs, there are no randomized clinical trials upon which to base treatment recommendations. After maximal safe resection, adult patients are treated with normofractionated CSI of 30-36 Gy followed by a tumor bed boost to 54-55.8 Gy and occasional chemotherapy, particularly for high-risk disease, with unknown outcomes [45,46]. However, such conventional radiation therapy is associated with progressive neurotoxicity, leading to the degradation of the quality of life.…”
Section: Chemotherapymentioning
confidence: 99%